Economic Analysis of Improving the Energy Efficiency of Nanogrid Solar Road Lighting Using Adaptive Lighting Control - Pathomthat Chiradeja; Suntiti Yoomak; Atthapol Ngaopitakkul (My University, 2020)
This paper presents a road lighting control system that uses a light-dependent resistor sensor cooperating with an Internet protocol camera to the lower energy consumption during unnecessary use of a lighting system. A microcontroller was used as a control circuit to automatically control the brightness of a light-emitting diode (LED) luminaire, increasing or decreasing the brightness depending on traffic density. The proposed lighting control system was integrated into a nanogrid solar road lighting system and analysed through an experimental setup. Furthermore, nanogrid solar road lighting systems in LED solar stand-alone and grid-connected operations, with and without the proposed lighting control, were investigated and compared with a conventional existing road lighting system in terms of economic feasibility, based on the following indicators: discounted payback period, net present value, internal rate of return, and profitability index. The results indicate that the use of the Internet protocol camera with the LED sensor can automatically control the on/off state or illuminance levels of the LED luminaire, thereby lowering the energy consumption of the road lighting system when lighting is not required. The economic assessment results indicate that the nanogrid solar road lighting system in LED solar stand-alone and grid-connected road lighting modes exhibit feasibility for investment; the latter provides more economic feasibility. However, when the proposed lighting control is included, the nanogrid solar road lighting system in both modes have lower initial investment costs and save more energy. Consequently, the economic results are improved. The use of the proposed lighting control is thus economically feasible for road lighting systems.
Keywords: Smart lighting; LED lamp; Impact of Light on Environment and Health